Penurunan Kadar Amonia Limbah Cair Menggunakan Adsorben Abu Terbang Bagas di Industri Penyamakan Kulit - Betryana Agnes Pratiwi; Darjati .; Pratiwi Hermiyanti (Poltekkes Kemenkes Surabaya, 2018)
The incidence of odor around the waste of the tannery industry is due to the high ammonia (NH3) content of 3.79 mg/l, so to lower the high levels of ammonia (NH3) it is necessary to process. The purpose of this research is to reduce ammonia (NH3) in the wastewater of tannery industry according to environmental quality standard. The method of this study was experimental, with Pretest-Posttest with control group design comparing ammonia decrease before and after processing, with treatment variation for 2 gram of adsorbent mass; 3 grams; 4 grams and contact time of 60 minutes; 90 minutes; 120 minutes. Measurement of ammonia (NH3) using a spectrophotometer. The highest percentage of ammonia (NH3) decline was 96.83% in a 4 gram treatment variation with 120 minutes contact time, with a decrease in ammonia value of 0.12 mg/l where the environmental quality standard of East Java Governor Regulation No. 52 of 2014 Ie 0.5 mg / l, so that the results meet the environmental quality standards. The results of statistical analysis showed that the most optimum is the mass of 4 gram adsorbent with contact time of 120 minutes. Suggestions for related industries can use the results of this study in the process of decreasing levels of ammonia (NH3) and for other researchers is expected to combine with other technologies to optimize the results in reducing levels of ammonia (NH3). Keywords : Fly ash, ammonia levels of liquid waste